Self-nitrogen-doped porous biochar derived from kapok (Ceiba insignis) fibers: Effect of pyrolysis temperature and high electrochemical performance. Issue 10 (October 2018) - Wang, Jun-Rui; Wan, Feng; Lü, Qiu-Feng; Chen, Fei; Lin, Qilang
Abstract: Self-nitrogen-doped porous biochar derived from kapok fibers possesses unique structure and excellent electrochemical performance. In this study, one-step pyrolysis method was introduced to prepare porous biochar from kapok fibers, and effect of pyrolysis temperature on structure and electrochemical performance of the porous biochar was investigated. It was found that pyrolysis temperature played an important role in determining microstructure of the biochar. At the pyrolysis temperature of 750 °C, the as-prepared biochar (CKF -750) represented a largest specific surface area of 1125.7 m 2 g −1 and pore volume of 0.7130 m 3 g −1, and hence brings CKF -750 a highest specific capacitance of 283 F g −1 at a current density of 1 A g −1 in a 6 mol L −1 KOH electrolyte. Furthermore, the cycle stability of CKF -750 was wonderful, and the specific capacitance retained almost constant after 10000 cycles. Therefore, the pyrolysis temperature of 750 °C is optimal for the preparation of porous biochar as an outstanding electrode material for supercapacitor.